ChemInform Abstract: Catalytic C—H Bond Addition of Pyridines to Allenes by a Rare‐Earth Catalyst. Issue 41 (October 2015) - Song, Guoyong; Wang, Baoli; Nishiura, Masayoshi; Hou, Zhaomin
Abstract A combination of a half‐sandwich scandium complex and [Ph3C][B(C6F5)4] catalyzes the addition reaction of diversely substituted pyridines with allenes to afford 2‐alkylpyridines stereoselectively.